Total vehicle technology : challenging current thinking - IMechE Automobile Division Southern Centre Conference on Total Vehicle Technology (1st : 2001 : Brighton, United Kingdom); Childs, P. R. N.; Stobart, R. K. (United Kingdom : Professional Engineering Publishing, 2001)
20